Application of Encapsulated Lactic Acid Bacteria in Goat Milk Set Yoghurt: Microbiological Characteristics - Archadiya, Meilan; Wafiroh, Muthiatin; Rahmawati, Dewi; Mufidah, Nisa (Jurnal Ilmu-Ilmu Peternakan, 2026)
This study aimed to determine the effect of the addition of encapsulated Lactobacillus bulgaricus FNCC 0035 and Streptococcus thermophilus FNCC 0040 additions on the microbiological quality, specifically the Total Plate Count (TPC), Lactic Acid Bacteria (LAB), Yeast and Mold Count (YMC), and antimicrobial activity of goat milk set yoghurt. The research was conducted using a laboratory experiment with a Completely Randomized Design (CRD) with four treatments, namely T0 (2% addition of non-encapsulated LAB starter), T1 (addition of 2% encapsulated LAB starter), T2 (addition of 3% encapsulated LAB starter), and T3 (addition of 4% encapsulated LAB starter), with four replicates each. Data analysis was performed using Analysis of Variance (ANOVA), and if there was a significant effect, it was further tested with Duncan's Multiple Range Test (DMRT). The results of the variance analysis showed that the addition of encapsulated LAB had a significant effect (P<0.05) on the microbiological characteristics of goat milk set yoghurt. Goat milk set yoghurt with the addition of 4% encapsulated LAB starter (T3) was the best treatment with an average TPC of 6.65 log cfu/ml, LAB 8.70 log cfu/ml, YMC of 1.80 log cfu/ml, antimicrobial activity against Escherichia coli bacteria of 0.90 mm, and antimicrobial activity against Staphylococcus aureus bacteria of 1.54 mm.